Tools, Techniques, and Methods of Finance and their Applications in Business - Mustafa, Sadaf (Advances in Social Sciences Research Journal, 2018)
Effective financial management involves intelligent use of financial tools, techniques and methods to determine and increase market value of firms. Its scope extends beyond accounting, budgeting, financial reporting and analysis. Its scope also goes beyond use of regular accounting tools like time value of money, working capital management, NPV analysis, make versus buy decisions, and investment analysis. In the broader domains of business, therefore, finance managers are expected to provide foresight for business strategy, helping the firms gain sustainable growth and expansion. The main purpose of this paper is to present and analyze the efficacy and relevance of the most pertinent tools used in the financial analysis. In order to achieve the purpose, secondary research is used to provide supporting evidence to determine the efficacy of each of the classical and contemporary financial tools. Extensive literature from research journals has been sought to present discussion on the relevance of these tools in light of growing changes in the world of finances, varying financial structures across the globe and rising need for ethical considerations in measurement and presentation of financial analysis and financial reports. This paper begins with a look at the basic valuation tools used by finance managers to assess a firm’s value. It then moves to analyze advanced financial tools need to create and sustain firm value. Finally, the paper presents an examination of the legal and ethical insights into the use of these tools and techniques and advocates measures that should be adopted by decision makers in finance.